2013
DOI: 10.1371/journal.pone.0073643
|View full text |Cite
|
Sign up to set email alerts
|

Antifreeze Protein Prolongs the Life-Time of Insulinoma Cells during Hypothermic Preservation

Abstract: It is sometimes desirable to preserve mammalian cells by hypothermia rather than freezing during short term transplantation. Here we found an ability of hypothermic (+4°C) preservation of fish antifreeze protein (AFP) against rat insulinoma cells denoted as RIN-5F. The preservation ability was compared between type I–III AFPs and antifreeze glycoprotein (AFGP), which could be recently mass-prepared by a developed technique utilizing the muscle homogenates, but not the blood serum, of cold-adapted fishes. For A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
(34 reference statements)
1
29
0
Order By: Relevance
“…It is believed that many freeze-tolerant organisms inhabiting cold environments have developed AFPs to ensure their survival [ 30 ]. Because AFPs are effective at inhibiting IR, they are beneficial for the cryopreservation of cells and tissues [ 20 , 31 33 ]. The current study compared the cryoprotective efficacy of three types of recombinant AFPs in the vitrification of mouse OT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that many freeze-tolerant organisms inhabiting cold environments have developed AFPs to ensure their survival [ 30 ]. Because AFPs are effective at inhibiting IR, they are beneficial for the cryopreservation of cells and tissues [ 20 , 31 33 ]. The current study compared the cryoprotective efficacy of three types of recombinant AFPs in the vitrification of mouse OT.…”
Section: Discussionmentioning
confidence: 99%
“…Although these IBPs have different TH activities, and they all inhibit IR, which cannot be quantitated. A variety of studies have reported diverse effects by AFPs on the hypothermal preservation of an insulinoma cell line [ 20 ], Escherichia coli [ 21 ], red blood cells [ 11 ], bovine sperm [ 22 ], and mouse oocytes [ 23 ]. Through these previous studies, we could assume that AFPs also have preventive effects of cryodamage even in the cryopreservation of OT.…”
Section: Introductionmentioning
confidence: 99%
“…AFP I is a low-molecular-weight protein (< 30 kDa) obtained from the barfin plaice (bp), also called the native bpAFP [19] with a molecular weight of 3.5 kDa [20]. AFGP was provided by Nichirei Co. Ltd. as a purified sample of AFGP from Eleginus gracilis [21] with an assumed molecular weight of 15 kDa [20]. The TH activity of AFP I was stated in 0.1 M ammonium bicarbonate (pH 7.9) at a concentration of 10 mg mL -1 .…”
Section: Th Activity Measurementmentioning
confidence: 99%
“…The ability of IBPs to prevent freezing and freeze injury in nature has current and potential uses. These include applications in the food industry (15); cryopreserva-tion and chill-storage of cells (16)(17)(18), tissues, and organs for transplantation (19); cryosurgery; preventing frost damage to plants (20); and anti-icing (21).…”
Section: Introductionmentioning
confidence: 99%